(untitled) (FULafia Journal of Science and Technology, 2025)
Despite the importance of urban greenery, research on trees in urban schools remains sparse. Hence, this study investigates woody plant diversity and carbon storage in three secondary schools in Lafia, Nasarawa State, Nigeria: Government Science School (GSS) Lafia, GSS Shabu, and GSS Tundun Kauri. Using systematic and random sampling, five plots per school were analyzed for tree diversity, with biomass measurement obtained through allometric equations. Tree diversity was quantified using Shannon and Simpson indices, while carbon storage and CO2 equivalent were calculated from the biomass data. At GSS Lafia, Plot 2 (West) had the highest species diversity (Shannon index: 1.367, Fisher’s alpha: 3.538), while Plot 5 (Central) had the lowest (Shannon index: 0.3488, Fisher’s alpha: 0.7972). At GSS Shabu, Plot 2 (West) had the highest diversity (Shannon index: 1.082, Simpson’s 1-D: 0.6563), whereas Plots 1 (East), 4 (North), and 5 (Central) had no diversity. GSS Tundun Kauri’s Plot 2 (West) showed the highest diversity (Shannon index: 0.6931, evenness: 1), while Plots 2, 4, and 5 had none. Regarding carbon storage, GSS Shabu’s Plot 2 (West) had the highest carbon storage of 15,3356.44 kg and CO2 equivalent of 562.31 tons. In contrast, Plot 5 (Central) at GSS Tundun Kauri had the lowest carbon storage with 16,535.68 kg and CO2 equivalent of 60.63 tons. GSS Lafia’s Plot 2 (West) contributed significantly with CO2 equivalent of 164.29 tons and carbon storage of 44,808 kg. These findings emphasize the need to maintain tree diversity for optimal carbon sequestration and urban green space management.